Smoothed particle hydrodynamics modelling of multiphase flows: an overview - Pozorski, Jacek; Olejnik, Michał (Acta mechanica, 2024)
Smoothed particle hydrodynamics (SPH) is a meshless, particle-based approach that has been increasingly applied for modelling of various fluid-flow phenomena. Concerning multiphase flow computations, an advantage of the Lagrangian SPH over Eulerian approaches is that the advection step is straightforward. Consequently, the interphasial surface can be explicitly determined from the positions of particles representing different phases; therefore, there is no need for the interface reconstruction step. In this review paper, we briefly recall the basics of the SPH approach, and in particular the physical modelling and numerical implementation issues. We also mention the weaknesses of the approach and some remedies to overcome them. Then, we demonstrate the applicability of SPH to selected interfacial flow cases, including the liquid column break-up, gas–liquid flow regimes in a channel capturing the transitions between them and the wetting phenomena. Concerning the two-fluid modelling, it is illustrated with sediment transport in the presence of surface waves. Various other applications are briefly recalled from the rich and growing literature on the subject, followed by a tentative list of challenges in multiphase SPH.